Disaster Nursing Competencies among Nurses Working in Tertiary Level Teaching Hospital in Kathmandu, Nepal - Hricha Neupane; Parikshit Chapagain (Journal of Karnali Academy of Health Sciences, 2021)
Background: Nepal is one of the most multi hazard prone countries in the world. The first responders and the largest health workforce of any country are nurses. Therefore, it is essential to determine the competencies of nurses, as one of the baseline for disaster preparedness. This study explores nurses’ current roles and responsibilities in disaster management, core competencies that need to be implemented and barriers to developing core competencies.